Internal growth of women with recurrent miscarriage: a qualitative descriptive study based on the post-traumatic growth theory - Gisoo Shin; Hye Jin Kim; Sung Hae Kim (BMC, 2023)
Abstract Background Unexpected and repeated miscarriages in a woman's life cycle can be a mental and physical burden and lead to post-traumatic stress disorder. However, women may also experience inner growth with such experiences. Methods This study was qualitative descriptive research examining the experiences of South Korean women who had recurrent miscarriages three or more times. Results The average age of the participants was 34.6 years, and the average number of recurrent miscarriages was 3.87. Additionally, five themes were identified as follows: (1) Confusing as if in muddy water, (2) Self-examination of past daily life, (3) Empathy and comfort in homogeneous groups, (4) Religious beliefs that include the lost fetus, and (5) Transforming for internal growth. Conclusion Based on the results of this study, intervention strategies need to be implemented to support the inner growth of women who have experienced recurrent miscarriages.